X-ray synchrotron study of liquid-vapor interfaces at short length scales: Effect of long-range forces and bending energies - Mecke, Klaus; et al. (Physical Review Letters, 2003)
We have investigated the small-scale structure of the liquid-vapor interface using synchrotron x-ray scattering for liquids with different molecular structures and interactions. The effective momentum-dependent surface energy first decreases from its macroscopic value due to the effect of long-range forces, and then increases with increasing wave vector. The results are analyzed using a recent density functional theory. The large wave-vector increase is attributed to a bending energy for which local and nonlocal contributions are equally important.